Thoughtless acts ? : observations on intuitive design. - Fulton Suri, Jane, ....- (San Francisco : Chronicle Books, 2005)
From IDEO, the global innovation and design firm responsible for such landmark products as Apple's first computer mouse, comes a primer in the observation method that keeps their practice human-centered and ever ingenious. People unconsciously perform ultraordinary actions every day, from throwing a jacket over a chair back to claim the seat, or placing something in the teeth when all hands are full. These "thoughtless acts" reveal the subtle but crucial ways people behave in a world not always perfectly tailored to their needs. Thoughtless Acts? is a collection of dozens of (often humorous) snapshots capturing such fleeting adaptations and minor exploitations. This method of observation demonstrates the kind of common-sense approach that can inspire designers and anyone involved in creative endeavors. Thoughtless Acts? is a privileged peek at how IDEO creates the people-friendly products, services, and spaces for which they are so widely recognized.